2005
DOI: 10.17221/5642-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

New probiotic strain Lactobacillus fermentum AD1 and its effect in Japanese quail

Abstract: ABSTRACT:Probiotics have been used with increasing frequency in nutrition and for prophylactic purposes during the last years. In the present study we investigated the effect of Lactobacillus fermentum AD1 -canine isolate on selected intestinal microbial groups, weight gain, organic acids, haematology, glutathione peroxidase and phagocytosis of leucocytes in 2-days-old Japanese quail (Coturnix coturnix japonica). The results demonstrated that the 4-day application of this strain significantly increased the pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
1
9
1
2
Order By: Relevance
“…Kong et al [38] reported a significant increase of the serum contents and an apparent ileal digestibility of most amino acids tested in weaned piglets supplemented with E. senticosus extract (0.1% of diet). Although protein metabolism and nitrogen retention was shown to support also some probiotic strains in animals [39] including strain CCM 7421 but after a shorter supplementation period [7,36], no increase was detected in the LF group in this study. The possible reason of the specifity to increase total protein might be connected with differences in the microflora abundance (e.g.…”
Section: Tp -Total Protein; Alb -Albumin; Trig -Triglyceride; Glu -Glcontrasting
confidence: 53%
See 1 more Smart Citation
“…Kong et al [38] reported a significant increase of the serum contents and an apparent ileal digestibility of most amino acids tested in weaned piglets supplemented with E. senticosus extract (0.1% of diet). Although protein metabolism and nitrogen retention was shown to support also some probiotic strains in animals [39] including strain CCM 7421 but after a shorter supplementation period [7,36], no increase was detected in the LF group in this study. The possible reason of the specifity to increase total protein might be connected with differences in the microflora abundance (e.g.…”
Section: Tp -Total Protein; Alb -Albumin; Trig -Triglyceride; Glu -Glcontrasting
confidence: 53%
“…In our study, a significant increase of PA was detected 2 (P<0.001) and 5 (P<0.01) weeks after cessation of probiotic application, but the probiotic strain still persisted in certain levels in faeces. A significant increase of PA (P<0.05) after 4-days application of L. fermentum CCM 7421 strain was observed in our previous study using newborn Japanese quail [36]. The immunostimulation of the respiratory burst of the sole phagocytes is a straindependent characteristic of probiotics and mostly only long-term probiotic treatments have lead to significant results [37].…”
Section: Tp -Total Protein; Alb -Albumin; Trig -Triglyceride; Glu -Glmentioning
confidence: 78%
“…After 24 h cultivation 200 μl of S. Enteritidis SE147 (provided by Dr. Rychlík, VRI, Brno, Czech Republic) in the number of 1 × 10 8 CFU/ml, and 200 μl of Enterococcus faecium AL41, Enterococcus faecium H31 and Lactobacillus fermentum AD1 (provided by Dr. Lauková, IAP SAS, Košice, Slovakia) in a number of 1 × 10 9 CFU/ml were added to PMBCs in particular wells. After the addition of bacteria PMBCs were cultured for 24 and 48 h. The cultivation of bacterial strains, culture medium and growth conditions was performed as described previously (Herich et al 2005;Strompfová et al 2005). …”
Section: Methodsmentioning
confidence: 99%
“…There are many studies reported on the beneficial use of certain LAB strains in animal feeding. For instance, the use of probiotic from strain Lactobacilus fermentum AD1 resulted in 14% weight gain in Japanese quail [7]. In addition to our previous works on LAB screening from various local sources such as fermented food [8], broiler chicken [9], rabbit [10] and catfishes [11]; this work reports on several LAB strains isolated from quail's intestine with the objective to identify the diversity of LABs in quail.…”
Section: Introductionmentioning
confidence: 99%